Asystasia venui (Justicieae: Acanthaceae): A new species from West Bengal, India - Kumar, Anant; Krishna, Gopal; Bhattacharjee, Avishek (Phytotaxa, 2023)
Asystasia venui (Justicieae: Acanthaceae), a new species is described and illustrated from West Bengal, India. Morphologically, it resembles A. atroviridis and A. neesiana, but differs from these two species in having smaller corolla tube and calyx lobes, papillose ovary, glandular hairy capsules, and papillose ovary, lax racemes with glandular pubescent rachis respectively. A detailed morphological description of Asystasia venui, together with photographs, comparative illustrations and a key to the species of Asystasia occurring in India is provided for identification.